ECO-PRESSING AS A RISK FACTOR OF UNWHOLESOME TUBERCULOSIS EPIDEMIOLOGIACAL DEVELOPMENT - V. S. Semechkina; E. U. Zorkaltsewa; O. A. Vorobiova (Acta Biomedica Scientifica, 2012)
Contrary tuberculosis epidemiology in the Irkutsk region is observed. There are a lot of factors underlain of this situation. Because of the Irkutsk region comprises a large amount of industrial sectors, we cannot ignore the role of anthropogenic impact. The aim. of the research was to study how epidemic process of pulmonary tuberculosis could manifest in conditions of technogenic pollution in large industrial cities in the Eastern Siberia. It was found that air pollution strongly effects to the formation of unfavorable respiratory tuberculosis epidemiology.